Adsorption of Methylene Blue and Reactive Black 5 by Activated Carbon Derived from Tamarind Seeds - Zaniah Ishak; Sa’diah Salim; Dilip Kumar (Tecno Scientifica Publishing, 2022)
One of the most environmentally friendly methods to treat wastewater, especially synthetic dyes, is the production of activated carbon from agricultural waste. Tamarind seeds were transformed from negative-value waste into activated carbon in order to study the removal of synthetic dyes. The particular agro waste was soaked in ZnCl2 for chemical activation to increase its surface area and enhance its porosity. Physical activation of tamarind seeds was done by the carbonization process by burning at a temperature of 300 °C for 1 hour and cooling for 24 hours before washing with HCL to activate a pore surface for the tamarind seeds' carbon. The effects of parameters related to the adsorption of the dyes by tamarind seed activated carbon, such as contact time, initial concentration, absorbance dosage, and pH, were studied. The experimental data found that adsorption on both synthetic dyes exhibited a Langmuir isotherm in which the correlation value, R2, was 0.9227 (methylene blue) and 0.6117 (Reactive black 5). Meanwhile, the rate of adsorption for methylene blue (MB) and Reactive black 5 (RB5) by tamarind seed activated carbon was found to be well fitted in a pseudo-second-order model. More research is needed to meet the standard effluent of dyeing wastewater from the industrial sector.